2015
DOI: 10.1007/s10035-015-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of anisotropy and non-coaxiality of granular solids

Abstract: Previous experimental studies of anisotropy and non-coaxiality by using the hollow cylindrical apparatus are mainly focused on granular soils, which feature irregular particle shapes and non-uniform particle size distributions. This paper experimentally investigates these two characteristics on assemblages of particulate materials with regular particle shapes and uniform particle sizes. These assemblages are made from spherical, cylindrical and cubical particles, with an increasing order of particle angularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Interesting granular phenomena like yielding and jamming (Liu and Nagel, 1998;Bi et al, 2011;Luding, 2016;Kumar and Luding, 2016), dilatancy (Cates et al, 2005;Van Hecke, 2009;Yang et al, 2015), shear-band localization (Alshibi and Sture, 2000;Singh et al, 2014), history-dependence (Thakur et al, 2014), and anisotropy (Radjai et al, 1996;Majmudar and Behringer, 2005) have attracted significant scientific interest over the past decades (Savage and Hutter, 1989;Cundall, 1989;Radjai et al, 1999;Wolf et al, 2000;† GDR-MiDi, 2004;Tomas, 2005;Alonso-Marroquin and Herrmann, 2004;Luding 2005aLuding , b, 2008. Various laboratory element tests can be performed to study the bulk behaviour of granular materials (Schwedes, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Interesting granular phenomena like yielding and jamming (Liu and Nagel, 1998;Bi et al, 2011;Luding, 2016;Kumar and Luding, 2016), dilatancy (Cates et al, 2005;Van Hecke, 2009;Yang et al, 2015), shear-band localization (Alshibi and Sture, 2000;Singh et al, 2014), history-dependence (Thakur et al, 2014), and anisotropy (Radjai et al, 1996;Majmudar and Behringer, 2005) have attracted significant scientific interest over the past decades (Savage and Hutter, 1989;Cundall, 1989;Radjai et al, 1999;Wolf et al, 2000;† GDR-MiDi, 2004;Tomas, 2005;Alonso-Marroquin and Herrmann, 2004;Luding 2005aLuding , b, 2008. Various laboratory element tests can be performed to study the bulk behaviour of granular materials (Schwedes, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the non‐coaxiality of granular media by experimental tests, theoretical analyses, and numerical simulations . As a result of the deposition process and grain characteristics, a granular soil can be inherently anisotropic .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the non‐coaxiality of granular media by experimental tests, theoretical analyses, and numerical simulations . As a result of the deposition process and grain characteristics, a granular soil can be inherently anisotropic . Experimental studies have strongly suggested that the inherent anisotropy contributes to the key aspects of many macroscopic sand responses, including dilatancy and non‐coaxiality .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations